Polyurethane-carbon microfiber composite coating for electrical heating of concrete pavement surfaces. Issue 8 (August 2019) - Sassani, Alireza; Arabzadeh, Ali; Ceylan, Halil; Kim, Sunghwan; Gopalakrishnan, Kasthurirangan; Taylor, Peter C.; Nahvi, Ali
Abstract: Electrically-heated pavements have attracted attention as alternatives to the traditional ice/snow removal practices. Electrically conductive polymer-carbon composite coatings provide promising properties for this application. Based on the concept of joule heating, the conductive composite can be utilized as a resistor that generates heat by electric current and increases the surface temperature to melt the ice and snow on the pavement surface. This research investigates the feasibility of applying an electrically conductive composite coating made with a Polyurethane (PU) binder and micrometer-scale carbon fiber (CMF) filler as the electrical heating materials on the surface of Portland cement concrete (PCC) pavements. PU-CMF composite coatings were prepared using different volume fractions of CMF, applied on the PCC surfaces, and evaluated in terms of volume conductivity, resistive heating ability, durability, and surface friction properties at the proof-of-concept level. A conceptual cost analysis was performed to compare this method with other heated pavement systems with respect to economic viability. Percolative behavior of CMF in PU matrix was captured and most desirable CMF dosage rates in terms of each performance parameter were investigated. Two percolation transition zones were identified for CMF in PU matrix at dosage rate ranges of 0.25–1% and 4–10%. The composites exhibited their most desirable performance and properties at CMF dosage rates greater than 10% and smaller than 15%.